Student Preferences for Group Size in a Language Development Course - Joshua Cohen (Networks: An Online Journal for Teacher Research, 2020)
Student preferences for group size were investigated. Pre- and post-study surveys, student written comments, and teacher observations were used to record changes in attitude and perception of group work while learning English over an eight-week period. In this study, I observed how arrangement impacted my students’ impressions of individual, pair, and group activities. My purpose for focusing on student configuration was twofold: firstly, I wanted to learn more about my students’ preferences for group size, and secondly; I wanted to find out whether certain combinations of students affected their perceptions of learning more than others.
Keywords: collaboration; interaction; group work; group size